Two-Degree-of-Freedom PID Controller, Its Equivalent Forms and Special cases - Haresh A. Suthar (Institute of Advanced Engineering and Science, 2015)
The design of control systems is a multi-objective problem so, a two-degree-of-freedom (abbreviated as 2DOF) control system naturally has advantages over a one degree- of-freedom (abbreviated as 1DOF) control system. The main objective of 2DOF control is to control both set point tracking and disturbance rejections.Various 2DOF PID controllers and its equivalent transformations were proposed for industrial use by different researchers. Most of the above researches were published in Japanese language and have not been translated into English language yet. An objective here is to provide detail analysis regarding structure of 2DOF controller, its equivalent forms and its special cases. A system transfer function having transport delay and load disturbance is considered as a test bench to verify various 2DOF control strategies. MATLAB is used as software tool to verify the various 2DOF control strategies. The analysis will be helpful to the engineers and researchers to understand the topic in detail for further exploration.